A Note on "Teaching Approaches to Elementary Accounting" . - Singer, Frank A. (The Accounting Review, 1966)
Abstract The article presents a discussion on the article "Teaching Approaches to Elementary Accounting," by Lloyd D. Doney and Richard C. Neumann, published in the July 1965 issue of the journal "The Accounting Review." The previous article had highlighted that the use of programmed learning material did not make any significant difference in performance of accounting students, which has been criticized in this article. The author holds that the exposure of students to few items on the evaluation test, prior to mid-semester exams, gave them a significant advantage. The fact can be elaborated by the argument that final examination performance on repeated items was improved about 40% at the University of Massachusetts. It is also noteworthy that the only performance equal even to the third of these was the top performance in the honors section at the University. Thus, it may be that programmed learning has a desirable impact on individual students, even where it does not seem to influence the average performance of the group.